Nationalism or supra-nationalism in the 21st Century? - Vhutuza, Ephraim; Ngoshi, Hazel T. (African Union Commission, 2016)
In the 21st century characterized by unprecedented information technology, mass communication, great strides in immigration and cultural differences, it is being argued that the world is moving towards larger units of human associations and global identities (supranationalism) which make nationalism with its defense of the local, wither away or at best continue to exist but in a minor and secondary role. The paper shall argue that although there are greater advances in information technology and mass communication, it is this same 'baggage' which nationalists over the world are using to instill and spread national values, sentiments and beliefs in their populations. Therefore, what will continue to witness is not the supersession and transcendence of nations and nationalism but the interdependence of nationalism and supranationalism. These two will continue to feed into each other and the suggestion that nationalism is obselete and fit for the dustbin of history is as fallacious as the notion that the 21st century is a 'post-national' age.